Effect of Twinning on Chinese and English Vocabulary Knowledge. Issue 6 (20th July 2020) - Wong, Simpson W.L.; Cheung, Him; Zheng, Mo; Yang, Xiujie; McBride, Catherine; Ho, Connie Suk‐Han; Leung, Judy Sze‐Man; Chow, Bonnie Wing‐Yin; Waye, Mary Miu Yee
Abstract : Vocabulary knowledge was tested in a native (Cantonese‐Chinese) and foreign (English) language in 150 twins and 150 singletons aged 6–11 years, matched on age, gender, grade level, nonverbal intelligence, parents' education, family income, and number of siblings and household members. The singletons clearly outperformed the twins on the native vocabulary, but this "twinning effect" was much less noticeable for the foreign vocabulary. The effect on English vocabulary was further reduced after exposure to English at home was controlled. Given that these participants learned most of their English in school rather than home, the present findings support the notion that the twinning effect is associated with increased competition for family interaction in twins compared with singletons.